Review of semantic research of adverbs of place in Lithuanian - Judžentytė, Gintarė (Lietuvių kalba, 2013)
Semantic investigations of adverbs of place in Lithuanian started in 1653, when in the first grammar of the Lithuanian language Danielius Kleinas offered a classification of adverbs of place that consisted of four semantic groups: 1) In Loco; 2) De Loco; 3) Per Locum; 4) Ad Locum. This semantic division remained unchanged for over two centuries, i.e. 17th – 18th century. The comparative-historical method that was introduced in the 19th century influenced Lithuanian linguistics and, as a result, such figures as A. Šleicheris, the author of the first theoretical Lithuanian language grammar and F. Kuršaitis, another author of an important grammar volume focused more on the origin of adverbs (of place) rather than their semantics. The 20th century in Lithuanian linguistics had still retained some reverberations of the 19th century, the author of the first standard Lithuanian grammar J. Jablonskis still pays more attention to the origin of adverbs of place and not its meanings. The most significant semantic research of adverbs of place in this century is considered to be K. Ulvydas’ analysis in the academic “grammar of the Lithuanian language” as it was the first one to provide a comprehensive description of what an adverb is in general as well as a definition of an adverb of place. In comparison to other grammars written earlier, this work provides the most extensive semantic classification of adverbs of place; in addition, it provides a detailed account of the meanings of adverbs of place, the overlaps of those meanings, etc. Along with grammars of Lithuanian, adverbs of place were extensively investigated in other scholarly works. The most important of them is B. Forsman’s monograph “Das baltische Adverb” which, in comparison to other works devoted to Lithuanian adverbs of place, provides a detailed analysis and description of the semantics of adverbs of place in Lithuanian: 1. B. Forssman was the first one to apply the notion of space in the investigation of Lithuanian adverbs of place; • he was the first one to research Lithuanian adverbs of place by naming an object in relation to which the place/location is described; • he was the first one to include the notion of deixis into the history of semantic research of Lithuanian adverbs of place; • he was the first one to distinguish the meanings of Lithuanian adverbs of place according to the manner of localisation and division of space.